2015
DOI: 10.1016/j.cplett.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Spectral signatures of semiconductor clusters: (CdSe)16 isomers

Abstract: a b s t r a c tThe sensitivity of several experimentally accessible properties to the geometrical structure of the semiconductor (CdSe) 16 cluster is explored by density functional theory. Our test set consists of eleven (CdSe) 16 isomers belonging to various topological groups. For all isomers, the UV-visible and IR spectra have been simulated and vertical and adiabatic ionization energies, adiabatic electron affinities, polarizabilities and hyperpolarizabilities have been computed. The hyperpolarizability is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…While these structures are similar, they have different point groups ( D 2 for (CdSe) 16 , T h for (CdS) 16 ). These structures are also similar to the structure used in the spectra calculation reported by Gutsev et al, although the point group is different. (CdS) 15 and (CdS) 18 are both tubelike, with the former being shorter.…”
Section: Minimum-energy Structures Of (Cdx) N Nanoclusterssupporting
confidence: 81%
“…While these structures are similar, they have different point groups ( D 2 for (CdSe) 16 , T h for (CdS) 16 ). These structures are also similar to the structure used in the spectra calculation reported by Gutsev et al, although the point group is different. (CdS) 15 and (CdS) 18 are both tubelike, with the former being shorter.…”
Section: Minimum-energy Structures Of (Cdx) N Nanoclusterssupporting
confidence: 81%
“…In most cases, where the experimental geometrical structure is unavailable, the results of measurements by several methods are required for unambiguous identification of isomers. 74 4.2. Interconversion of Isomers.…”
Section: Results Of Computationsmentioning
confidence: 99%
“…Our previous study 40 of this dimer has showed that the BPW91/6‐311 + G* approach provides results comparable in accuracy to those obtained by the CCSD(T) method 41 whose results compare well to the experimental data. This functional has shown good performance for related chalcogenide II‐VI semiconductor clusters (CdS) n 42 and (CdSe) n , 43 and the experimental magnetic properties for ZnSe quantum dots doped 5 with Fe have been accurately predicted using this functional. The BPW91 method has been shown to perform quite well in predicting bond energies of a diverse variety of systems when tested against other functionals 44 .…”
Section: Details Of Computationsmentioning
confidence: 92%